High-strength and high-toughness carbon ceramic brake disc and preparation method thereof
Through direct pressurization molding process and silicon-resistant carbon fiber protective coating treatment, the problems of complex manufacturing processes, high cost and large material waste in traditional carbon ceramic brake discs are solved, and high strength and high toughness carbon ceramic brake disc preparation is realized, with the advantages of low cost, rapid molding and high mechanical performance.
Patent Information
- Application Number
- CN202510045955.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-13
- Publication Date
- 2025-03-14
AI Technical Summary
Traditional carbon ceramic brake discs have complex manufacturing processes, high costs, large waste of materials and long preparation cycles, making it difficult to meet the requirements of quickly responding to market demand.
Using the direct pressurization molding process, the carbon fiber is placed in a carbon fiber protective coating that is resistant to silicon corrosion and is heat treated to form a hard protective film, and then mixed evenly with the binder and resin, perform one-time molding and high-temperature treatment, and finally silicon-permeable treatment.
It significantly simplifies the production process, shortens molding and heat treatment time, reduces material waste and processing complexity, reduces production costs, improves product consistency and mechanical properties, and can perform reliably under high load and extreme conditions.
Smart Images

Figure CN119613137A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of carbon-ceramic brake disc preparation, and specifically relates to a high-strength and high-toughness carbon-ceramic brake disc and a preparation method thereof. Background Art
[0002] Carbon ceramic brake discs have become the preferred material for high-performance brake systems due to their excellent heat resistance, corrosion resistance, light weight and excellent wear resistance. These characteristics enable carbon ceramic brake discs to maintain stable performance even under extreme conditions, so they are widely used in high-end sports cars, racing cars, and aviation fields, which have extremely high requirements for braking systems. However, in the manufacturing process of traditional carbon ceramic brake discs, due to the use of 2.5D needle-punched preform molding technology, the process is relatively cumbersome and the cost is relatively high. This traditional manufacturing method not only requires multiple complex steps, but also about 35% of the high-quality carbon fiber materials will be cut off during the processing process, resulting in a large amount of material waste, which undoubtedly increases the economic burden of production.
[0003] In addition, the long preparation cycle is also an important factor restricting the large-scale popularization of carbon ceramic brake discs. The entire production process from raw material preparation to the final product may take weeks or even longer, which is a big challenge for manufacturers who seek to respond quickly to market demand. The long production process not only limits the supply speed of the product, but may also lead to a lag in market response, affecting the competitiveness of the company.
[0004] In the prior art, the preparation of carbon ceramic brake discs usually adopts the needle punching process of multi-layer carbon fiber, which is constructed layer by layer to achieve the required thickness and structural strength. Although this method can ensure that the product has good mechanical properties to a certain extent, its disadvantages are also obvious: the process is complicated, the quality consistency of the finished product is poor, and it is difficult to ensure that each carbon ceramic brake disc has completely consistent quality standards. In addition, during the siliconization step, there will be the problem of silicon eroding the surface of the carbon fiber, which is prone to local defects or uneven mechanical properties, which have a negative impact on its mechanical properties.
[0005] Therefore, it is necessary to provide a low-cost, rapid prototyping carbon-ceramic brake disc preparation technology to reduce production costs, reduce material waste and shorten the manufacturing cycle while taking into account its high strength and toughness properties. Summary of the invention
[0006] In order to solve the problems existing in the prior art, the object of the present invention is to provide a high-strength and high-toughness carbon-ceramic brake disc and a preparation method thereof.
[0007] The technical solution of the present invention is:
[0008] A method for preparing a high-strength and high-toughness carbon ceramic brake disc comprises the following preparation steps:
[0009] S1, placing the carbon fiber in a carbon fiber protective coating resistant to silicon corrosion and immersing it in a vacuum, taking it out and air-drying it, and then performing a heat treatment to obtain a coated carbon fiber;
[0010] S2, uniformly mixing the coated carbon fiber obtained in step S1 with a binder, drying at 80° C. to obtain a secondary fiber-wrapped mixture, and then soaking the mixture in a phenolic resin to allow the mixture to fully absorb the resin, then taking the mixture out for drying and curing the resin to obtain a preform rough embryo;
[0011] S3, heating the brake disc mold and maintaining a constant temperature, then placing the preform blank obtained in step S2 into the mold, pressurizing and curing the preform so that the blank is formed in one step to obtain a brake disc preform;
[0012] S4, subjecting the brake disc preform obtained in step S3 to high temperature treatment, and then subjecting it to siliconization treatment, to obtain a high-strength and high-toughness carbon ceramic brake disc.
[0013] Furthermore, the silicon-resistant carbon fiber protective coating in step S1 includes the following components and their weight proportions:
[0014] 15-30 parts of polynitrosilane, 15-25 parts of ethanol, 20-30 parts of boron nitride, and 15-30 parts of bismaleimide resin.
[0015] Furthermore, the silicon-resistant carbon fiber protective coating in step S1 is composed of the following components in parts by weight:
[0016] 25 parts of polynitrosilane, 20 parts of ethanol, 25 parts of boron nitride, and 24 parts of bismaleimide resin.
[0017] Furthermore, the concentration of the ethanol is ≥95%; and the particle size of the boron nitride is 0.1-0.3 μm.
[0018] Furthermore, the method for preparing the silicon-resistant carbon fiber protective coating comprises the following steps:
[0019] Add polynitrosilane, ethanol, boron nitride and bismaleimide resin into a grinder, add grinding balls, set the speed to 10-20 r / min, and grind for 5-8 hours to obtain the product.
[0020] Furthermore, the vacuum degree during vacuum immersion in step S1 is 10-40 kPa, preferably 30 kPa, the time is 15-20 min, and the temperature is 25-35°C.
[0021] Furthermore, after air drying in step S1, a protective film with a thickness of 5 to 10 μm is formed on the surface of the carbon fiber.
[0022] Furthermore, in the step S1, the temperature of the heat treatment after air drying is 900-1100° C., preferably 1000° C., and the time is 2-4 hours.
[0023] Furthermore, in step S2, the binder is one of polynitrogen silane, epoxy resin, and phenolic resin, preferably polynitrogen silane.
[0024] Furthermore, the polynitrogen silane is a silane binder, which is an organic-inorganic polymer of nitrogen element, and its structure usually contains Si-N bonds, which is conducive to the formation of a bonding interface between the carbon fiber shell and silicon, and can protect the fiber from being corroded by silicon during the siliconization process.
[0025] Furthermore, in step S2, the weight ratio of the coated carbon fiber to the binder is 6-7:3-4, preferably 6.5:3.5.
[0026] Furthermore, the resin used for soaking in step S2 is phenolic resin, which has good bonding strength at low temperature and high temperature carbon residue rate.
[0027] Furthermore, in step S2, the mixture is immersed in the phenolic resin for 30 to 60 minutes to allow it to fully absorb the resin, then taken out and air-dried, or placed in a drying oven at 120 to 160° C. to solidify the resin.
[0028] Furthermore, in step S3, the brake disc mold is heated to 180-220° C. and maintained at a constant temperature.
[0029] Furthermore, the initial density of the preform blank when placed into the brake disc mold in step S3 is 1.4-1.5 g / cm 3 .
[0030] Furthermore, during the pressurized curing process of step S3, 60-100 kg / cm 2 and maintain the pressure for 1 to 2 hours to form the rough blank in one go.
[0031] Furthermore, the high temperature treatment process in step S4 is as follows: placing the brake disc preform obtained in step S3 in a high temperature furnace for high temperature carbonization treatment, heating at a rate of 80-120°C / h when the temperature is below 1200°C, and heating to 2000°C at a rate of 200-300°C / h after exceeding 1200°C. After high temperature treatment, the density of the brake disc preform is 1.3-1.4 g / cm 3 .
[0032] Furthermore, the process of siliconizing treatment in step S4 is as follows: placing the brake disc preform in a graphite crucible, adding an appropriate amount of silicon powder, putting it into a vacuum sintering furnace, and rapidly heating it to 1500-1700°C and a vacuum degree of 100-1000Pa. At this time, the silicon material melts into the gaps in the brake disc blank and reacts with the resin carbon to form silicon carbide. After keeping the temperature for 2-4 hours, the temperature can be lowered to complete the siliconizing process.
[0033] The present invention proposes an innovative direct pressure-molding carbon ceramic brake disc preparation process, which avoids the layer-by-layer construction method in the traditional 2.5D needle punching process, greatly simplifies the production process, and greatly shortens the molding and heat treatment time compared to the traditional process, and significantly improves the production efficiency. In addition, the direct pressure molding process of the present invention molds the embryo in the mold at one time, reducing the multiple processing of the material, significantly reducing material waste and processing complexity, significantly reducing about 35% of material waste, greatly saving costs, and ensuring the consistency and stability of the product.
[0034] The present invention places carbon fiber in a specific carbon fiber protective coating resistant to silicon erosion for vacuum immersion, so that a protective film can be formed on the surface of the carbon fiber, and then heat-treated so that it can self-react at 900-1100°C to form a hard and airtight shell, which is used to resist the phenomenon of silicon material melting and corroding the carbon fiber during siliconization at 1450°C, prevent silicon from directly contacting the carbon fiber, avoid damage to the carbon fiber, maintain the maximum toughness and strength of the carbon fiber, and ensure the excellent mechanical properties of the carbon-ceramic brake disc under high temperature conditions; and the presence of the protective coating prolongs the service life of the carbon fiber, reduces the aging and wear of the material, thereby improving the durability of the entire carbon-ceramic brake disc.
[0035] The test shows that the carbon ceramic brake disc material prepared by the present invention exhibits excellent mechanical properties, especially in terms of tensile strength. The tensile strength of the finished product can reach 60-70MPa, and the fracture toughness is 4-6MPa·m1 / 2 , far exceeding the products prepared by traditional processes. This high strength property makes the carbon ceramic brake disc more reliable under high loads and extreme conditions, and can effectively meet the requirements of high-performance vehicles (such as racing cars, luxury cars, etc.) for the braking system. At the same time, the good mechanical properties extend the service life of the carbon ceramic brake disc prepared by the present invention.
[0036] Compared with the prior art, the high-strength and high-toughness carbon ceramic brake disc provided by the present invention has the following advantages:
[0037] The high-strength and high-toughness carbon ceramic brake disc provided by the present invention has low cost, can be quickly formed, has high tensile strength and fracture toughness, and is not only suitable for the manufacture of brake discs in the fields of high-performance automobiles, racing cars, and aviation, but can also be promoted in other industrial fields that require high-performance, high-wear-resistant, and high-heat-resistant components. By significantly reducing manufacturing costs and shortening production cycles, the application of carbon ceramic brake discs can be promoted in a wider market. BRIEF DESCRIPTION OF THE DRAWINGS
[0038] Figure 1 This is a scanning electron microscope (SEM) image of the carbon ceramic brake disc prepared in Example 2 of the present invention;
[0039] Figure 2 This is a scanning electron microscope (SEM) image of the carbon ceramic brake disc prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0040] The present invention is further illustrated below through the description of specific implementation methods, but this is not a limitation of the present invention. Those skilled in the art can make various modifications or improvements based on the basic idea of the present invention, but as long as they do not deviate from the basic idea of the present invention, they are all within the protection scope of the present invention.
[0041] In the following examples and comparative examples, reagents not otherwise specified are conventional reagents and can be purchased from conventional reagent production and sales companies. The methods used, unless otherwise specified, are all prior art. Information such as some raw material manufacturers is shown in Table 1:
[0042] Table 1
[0043] raw material Product Information Carbon Fiber Zhongfu Shenying SYT49S Polysilane CAS No.: 475645-84-2 purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd. Polycarbosilane Item No.: SLF-PCS, purchased from Suzhou Sailifei Company Bismaleimide resin Item No.: PFB301, purchased from Jinan Shengquan Group Co., Ltd. Epoxy resin Item No.: SQE-1401A75, purchased from Jinan Shengquan Group Co., Ltd. Phenolic resin Item No.: PF6710, purchased from Jinan Shengquan Group Co., Ltd.
[0044] Example 1
[0045] A method for preparing a high-strength and high-toughness carbon ceramic brake disc comprises the following preparation steps:
[0046] S1. Soak the carbon fiber in a carbon fiber protective coating resistant to silicon corrosion at a vacuum degree of 10 kPa and a temperature of 35°C for 20 minutes, take it out and air-dry it in a hot air oven, at which time a protective film of 5 to 10 μm thick is formed on the surface of the carbon fiber, and then heat it at a temperature of 900°C for 4 hours to make the protective film self-react to form a hard and airtight shell, thereby obtaining the coated carbon fiber;
[0047] The silicon-resistant carbon fiber protective coating in step S1 is composed of the following components in parts by weight:
[0048] 15 parts of polynitrogen silane, 15 parts of 95% ethanol, 20 parts of boron nitride (particle size 0.1 μm), and 15 parts of bismaleimide resin;
[0049] The method for preparing the silicon-resistant carbon fiber protective coating comprises the following steps:
[0050] Add polynitrosilane, ethanol, boron nitride and bismaleimide resin into a grinder, add grinding balls, set the speed to 10 r / min, and grind for 8 hours to obtain the product.
[0051] S2, uniformly mixing the coated carbon fiber obtained in step S1 with epoxy resin, wherein the weight ratio of the coated carbon fiber to the epoxy resin is 6:4, and then drying at 80° C. to obtain a fiber secondary wrapping mixture, and then soaking it in phenolic resin for 30 minutes to allow it to fully absorb the resin, taking it out to dry, and curing the resin to obtain a preform rough embryo;
[0052] S3, heat the brake disc mold to 180°C and keep the temperature constant, then put the preform blank obtained in step S2 into the mold. At this time, the initial density of the preform blank is 1.4g / cm 3 Then apply 60Kg / cm 2 The pressure is maintained for 2 hours for pressurized curing, so that the rough blank is formed in one step to obtain a brake disc preform;
[0053] S4, subjecting the brake disc preform obtained in step S3 to high temperature carbonization treatment, heating at a rate of 80°C / h when the temperature is below 1200°C, and heating to 2000°C at a rate of 200°C / h when the temperature exceeds 1200°C. After the treatment, the density of the brake disc preform is 1.3 g / cm 3 ;
[0054] Then siliconization treatment is carried out: the brake disc preform is placed in a graphite crucible, and an appropriate amount of silicon powder is added. It is put into a vacuum sintering furnace and quickly heated to 1500°C and a vacuum degree of 200Pa. At this time, the silicon material melts into the gaps in the brake disc blank and reacts with the resin carbon to form silicon carbide. After keeping warm for 4 hours, the temperature is lowered to complete the siliconization process, and a high-strength and high-toughness carbon ceramic brake disc is obtained.
[0055] Example 2
[0056] A method for preparing a high-strength and high-toughness carbon ceramic brake disc comprises the following preparation steps:
[0057] S1. Soak the carbon fiber in a carbon fiber protective coating resistant to silicon corrosion at a vacuum degree of 30 kPa and a temperature of 30°C for 18 minutes, take it out and air-dry it in a hot air oven, at which time a protective film of 5 to 10 μm thick is formed on the surface of the carbon fiber, and then heat it at a temperature of 1000°C for 3 hours to make the protective film self-react to form a hard and airtight shell, thereby obtaining the coated carbon fiber;
[0058] The silicon-resistant carbon fiber protective coating is composed of the following components in parts by weight:
[0059] 25 parts of polynitrogen silane, 20 parts of ethanol, 25 parts of boron nitride (particle size 0.2 μm), 24 parts of bismaleimide resin;
[0060] The method for preparing the silicon-resistant carbon fiber protective coating comprises the following steps:
[0061] Add polynitrosilane, ethanol, boron nitride and bismaleimide resin into a grinder, add grinding balls, set the speed to 15 r / min, and grind for 7 hours to obtain the product.
[0062] S2, uniformly mixing the coated carbon fiber obtained in step S1 with polynitrogen silane, wherein the weight ratio of the coated carbon fiber to the polynitrogen silane is 6.5:3.5, and then drying at 80° C. to obtain a secondary fiber wrapping mixture, and then soaking it in phenolic resin for 45 minutes to fully absorb the resin, taking it out and drying it at 120° C. to cure the resin to obtain a preform rough embryo;
[0063] S3, heat the brake disc mold to 200°C and keep the temperature constant, then put the preform blank obtained in step S2 into the mold. At this time, the initial density of the preform blank is 1.5g / cm 3 Then apply 80Kg / cm 2 The pressure is maintained for 1.5 hours for pressurized curing, so that the rough blank is formed in one step to obtain a brake disc preform;
[0064] S4, subjecting the brake disc preform obtained in step S3 to high temperature carbonization treatment, heating at a rate of 100°C / h when the temperature is below 1200°C, and heating to 2000°C at a rate of 250°C / h when the temperature exceeds 1200°C. After the treatment, the density of the brake disc preform is 1.4 g / cm 3 ;
[0065] Then siliconization treatment is carried out: the brake disc preform is placed in a graphite crucible, and an appropriate amount of silicon powder is added. It is put into a vacuum sintering furnace and quickly heated to 1600°C and a vacuum degree of 600Pa. At this time, the silicon material melts into the gaps in the brake disc blank and reacts with the resin carbon to form silicon carbide. After keeping warm for 3 hours, the temperature is lowered to complete the siliconization process, and a high-strength and high-toughness carbon ceramic brake disc is obtained.
[0066] The carbon ceramic brake disc prepared in Example 2 of the present invention was photographed under a scanning electron microscope. Figure 1 ,from Figure 1 It can be clearly seen that the carbon fiber coating is protecting it. The silvery-white silicon does not adhere to the carbon fiber and does not corrode the fiber, which is the main reason for ensuring the fiber strength.
[0067] Example 3
[0068] A method for preparing a high-strength and high-toughness carbon ceramic brake disc comprises the following preparation steps:
[0069] S1. Soak the carbon fiber in a carbon fiber protective coating resistant to silicon corrosion at a vacuum degree of 40 kPa and a temperature of 25°C for 15 minutes, take it out and air-dry it in a hot air oven, at which time a protective film of 5 to 10 μm thick is formed on the surface of the carbon fiber, and then heat it at a temperature of 1100°C for 2 hours to make the protective film self-react to form a hard and airtight shell, thereby obtaining the coated carbon fiber;
[0070] The silicon-resistant carbon fiber protective coating in step S1 is composed of the following components in parts by weight:
[0071] 30 parts of polynitrogen silane, 25 parts of 95% ethanol, 30 parts of boron nitride (particle size 0.3 μm), and 30 parts of bismaleimide resin;
[0072] The method for preparing the silicon-resistant carbon fiber protective coating comprises the following steps:
[0073] Add polynitrosilane, ethanol, boron nitride and bismaleimide resin into a grinder, add grinding balls, set the speed to 20 r / min, and grind for 5 hours to obtain the product.
[0074] S2, uniformly mixing the coated carbon fiber obtained in step S1 with a phenolic resin, wherein the weight ratio of the coated carbon fiber to the phenolic resin is 7:3, and then drying at 80° C. to obtain a fiber secondary wrapping mixture, and then soaking it in the phenolic resin for 60 minutes to allow it to fully absorb the resin, taking it out and drying it at 160° C. to solidify the resin, and obtaining a preform rough embryo;
[0075] S3, heat the brake disc mold to 220°C and keep the temperature constant, then put the preform blank obtained in step S2 into the mold. At this time, the initial density of the preform blank is 1.5g / cm 3 , then apply 100Kg / cm 2 The pressure is maintained for 1 hour for pressurized curing, so that the rough blank is formed in one step to obtain a brake disc preform;
[0076] S4, subjecting the brake disc preform obtained in step S3 to high temperature carbonization treatment, heating at a rate of 120°C / h when the temperature is below 1200°C, and heating to 2000°C at a rate of 300°C / h when the temperature exceeds 1200°C. After the treatment, the density of the brake disc preform is 1.4 g / cm 3 ;
[0077] Then siliconizing treatment is carried out: the brake disc preform is placed in a graphite crucible, and an appropriate amount of silicon powder is added. It is put into a vacuum sintering furnace and quickly heated to 1700°C and a vacuum degree of 1000Pa. At this time, the silicon material melts into the gaps in the brake disc blank and reacts with the resin carbon to form silicon carbide. After keeping warm for 2 hours, the temperature is lowered to complete the siliconizing process, and a high-strength and high-toughness carbon ceramic brake disc is obtained.
[0078] Comparative Example 1
[0079] Compared with Example 2, the difference is that the boron nitride powder in the silicon-resistant carbon fiber protective coating in step S1 is replaced with aluminum oxide powder (particle size is 0.2 μm), and the other components and preparation method are the same as those in Example 2.
[0080] The carbon ceramic brake disc prepared in Comparative Example 1 of the present invention was photographed under a scanning electron microscope. Figure 2 , Figure 2 It is obvious that cracks appear in the coating around the carbon fiber. During siliconization, the silicon material penetrates from the gaps and directly contacts the carbon fiber, causing the outer side of the carbon fiber to be corroded.
[0081] Comparative Example 2
[0082] Compared with Example 2, the difference is that the amount of boron nitride in the anti-silicon corrosion carbon fiber protective coating in step S1 is reduced to 15 parts, and the amount of polynitrogen silane is increased to 35 parts accordingly. The other components and preparation method are the same as those in Example 2.
[0083] Comparative Example 3
[0084] Compared with Example 2, the difference is that the binder polynitrosilane in step S2 is replaced by polycarbosilane, and the other components and preparation method are the same as those in Example 2.
[0085] Test Example 1: Performance test of the carbon ceramic brake disc prepared by the present invention
[0086] 1. Test object: carbon ceramic brake discs prepared in Examples 1 to 3 and Comparative Examples 1 to 3 of the present invention.
[0087] 2. Test method: Referring to the test method in Table 2, the density, bending strength, compressive strength, impact toughness, tensile strength, fracture toughness, rotational strength and other properties of the carbon ceramic brake discs prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were tested respectively. The test results are shown in Table 3.
[0088] Table 2
[0089]
[0090]
[0091] Table 3
[0092] Group Example 1 Example 2 Example 3 Comparative Example 1 Comparative Example 2 Comparative Example 3 <![CDATA[Density (g / m 3 )]]> 2 2.1 2.1 2.2 2.1 2.2 Bending strength(Mpa) 63 65 64 50 60 55 Compressive strength(Mpa) 210 215 213 191 203 200 <![CDATA[Impact toughness (kJ / m 2 )]]> 10 13 12 8 11 9 Tensile strength(Mpa) 68 70 67 50 60 60 <![CDATA[Fracture toughness (MPa·m1 / 2 )]]> 5.5 6 4.8 4.1 5.3 4.5 Rotational strength (r / min) 5500 5700 5600 4000 5000 4700
[0093] As shown in Table 3, the high-strength and high-toughness carbon ceramic brake discs prepared in Examples 1 to 3 of the present invention have a tensile strength of 60 to 70 MPa and a fracture toughness of 4 to 6 MPa·m1 / 2 , has excellent mechanical properties, can withstand high loads and extreme conditions to perform more reliably, and can effectively meet the requirements of high-performance vehicles (such as racing cars, luxury cars, etc.) for the braking system. When the preparation process of the carbon ceramic brake disc in the present invention is changed in Comparative Examples 1 to 3, the various properties of the obtained products have decreased to varying degrees.
[0094] The above embodiments are merely illustrative of the principles and effects of the present invention, and are not intended to limit the present invention. Anyone familiar with the art may modify or alter the above embodiments without departing from the spirit and scope of the present invention. Therefore, all equivalent modifications or alterations made by a person of ordinary skill in the art without departing from the spirit and technical concept disclosed by the present invention shall still be covered by the claims of the present invention.
Claims
1. A method for preparing a high-strength and high-toughness carbon ceramic brake disc, characterized in that: The method comprises the following preparation steps: S1, placing the carbon fiber in a carbon fiber protective coating resistant to silicon corrosion and immersing it in a vacuum, taking it out and air-drying it, and then performing a heat treatment to obtain a coated carbon fiber; S2, uniformly mixing the coated carbon fiber obtained in step S1 with a binder, and then drying to obtain a fiber secondary wrapping mixture, and then soaking it in a phenolic resin to allow it to fully absorb the resin, and then taking it out to dry and solidify the resin to obtain a preform rough embryo; S3, heating the brake disc mold and maintaining a constant temperature, then placing the preform blank obtained in step S2 into the mold, pressurizing and curing the preform so that the blank is formed in one step to obtain a brake disc preform; S4, subjecting the brake disc preform obtained in step S3 to high temperature treatment, and then subjecting it to siliconization treatment, to obtain a high-strength and high-toughness carbon ceramic brake disc.
2. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The silicon-resistant carbon fiber protective coating in step S1 includes the following components and their weight proportions: 15-30 parts of polynitrosilane, 15-25 parts of ethanol, 20-30 parts of boron nitride, and 15-30 parts of bismaleimide resin.
3. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The concentration of the ethanol is ≥95%, and the particle size of the boron nitride is 0.1-0.3 μm.
4. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The vacuum degree during vacuum soaking in step S1 is 10-40 kPa, the time is 15-20 min, and the temperature is 25-35°C.
5. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: After air drying in step S1, a protective film with a thickness of 5 to 10 μm is formed on the surface of the carbon fiber; the temperature of the heating treatment after air drying is 900 to 1100° C. and the time is 2 to 4 hours.
6. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: In the step S2, the binder is one of polynitrogen silane, epoxy resin and phenolic resin.
7. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: In the step S2, the weight ratio of the coated carbon fiber to the binder is 6-7:3-4.
8. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The initial density of the preform blank when placed into the brake disc mold in step S3 is 1.4-1.5 g / cm 3 During the pressurized curing process, 60 to 100 kg / cm 2 and maintain the pressure for 1 to 2 hours to form the rough blank in one go.
9. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The high temperature treatment process in step S4 is as follows: placing the brake disc preform obtained in step S3 in a high temperature furnace for high temperature carbonization treatment, heating at a rate of 80-120°C / h when the temperature is below 1200°C, and heating to 2000°C at a rate of 200-300°C / h when the temperature exceeds 1200°C. After high temperature treatment, the density of the brake disc preform is 1.3-1.4 g / cm 3 .
10. The method for preparing a high-strength and high-toughness carbon ceramic brake disc according to claim 1, characterized in that: The process of siliconizing treatment in step S4 is as follows: placing the brake disc preform in a graphite crucible, adding silicon powder, putting it into a vacuum sintering furnace, rapidly heating it to 1500-1700°C, with a vacuum degree of 100-1000Pa, and then cooling it after keeping it warm for 2-4 hours to complete the siliconizing process.